Hubungan antara Neuroticism dengan Perilaku Phubbing pada Mahasiswa Universitas Negeri Padang - Ramadhan, Ibnu Hatta; Rusli, Devi (Lembaga Yasin AlSys, 2024)
This study aims to determine the correlation between neuroticism and phubbing behavior in students at Padang State University. The type of research is quantitative correlational. Sampling was based on purposive sampling with a total of 270 respondents at Padang State University. The research scale uses the phubbing scale. The phubbing scale developed by Chotpitayasunond and Douglas (2018), namely the Generic Scale of Phubbing (GSP) which has been tested and translated by Isrofin (2020) and Jihan & Rusli (2019), the scale is adapted from the big five inventory scale ( BFI) which has been adapted to language and culture by Ramdhani (2012). The product moment correlation test was carried out to test the research hypothesis. The conclusion of this research is that there is a significant positive relationship between neuroticism and phubbing behavior in Padang State University students.